Architecture, City and Territory at the End of Enlightenment - Carlos SAMBRICIO (Cuadernos Dieciochistas)
Unlike those who identify the beginning of «Enlightenment Architecture» with the influence that Roman Classicism could have had at the advent of the second half of the Eighteenth Century, perhaps it is worth clarifying that between the critique of the Baroque and the adoption of such models lies a period of more than thirty years. In other words, unlike those who understand and confront the history of architecture or urban planning as a succession of styles it might be worth considering how the switch from one type of approach to another was not sudden but that previous suppositions coexisted and overlapped with the genesis of new ways of planning.